Penatausahaan Barang Milik Negara di Balai Wilayah Sungai Sulawesi III Palu - Sakinah; Rivai, Abdul; Salingkat, Syarif Permana (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
This study aims to examine the administration of State-Owned Assets (BMN) at the Sulawesi River Basin Agency III Palu, using the BMN administration concept by Suwanda and Rusfiana, which includes the aspects of bookkeeping, inventory, and reporting, particularly in the management of office stationery supplies (ATK). This research employs a qualitative method with a descriptive approach, and data collection techniques through observation, interviews, and documentation. The research informants consist of the Head of General Affairs Subdivision, Commitment Making Officer (PPK), BMN Manager, and BMN Operator. The results show that the administration of BMN has not been optimal due to the lack of human resource competencies, which leads to data discrepancies, lack of accuracy in record-keeping, weak coordination, and limited technical understanding. Therefore, there is a need to enhance human resource capacity, conduct more routine inventories, and strengthen oversight systems and information integration. This study recommends continuous technical training and the refinement of operational procedures to support more orderly and accountable BMN administration.